Lebanese Phalangism and fascism: history of a symbolic appropriation - Thuselt, Christian (Middle Eastern Studies, 2022)
This article discusses the alleged ideological roots of the Lebanese Phalanges party. It refutes both the reproach of the party being patterned after the Spanish Francoist model as well as the apologetics of having had no further ties to fascisms at all. Instead, the article argues, the Lebanese Phalangists held a thoroughly objectivist version of a united society, defined by their own ‘untouchable resources’. Therein they shared similarities to fascism, yet, established a genuine transformation by adopting symbols, concepts, and narratives that had been taken inter alia from Western fascist models, while omitting other elements, as suited their situation.
CRIS-Team Scopus Importer:2022-05-20
Keywords: culture; Politics; religion